Services Quality of Islamic Banking: An Investigation in Tripoli, Libya - Abuhelgha, Suhaib (2010)
The objective of this study is to examine the influence of service quality dimensions namely, tangibility,reliability, responsiveness, assurance, and empathy, of Islamic banking on customer satisfaction. Questionnaires are designed and distributed to customers of an Islamic bank in Tripoli, Libya. Multivariate statistical analysis is performed to analyze the data of this study. The results of the regression analyses indicate that all of the five hypotheses tested are supported. There is a positive effect and significant relationships between the five dimensions of service quality and customer satisfaction. The direct positive and significant relationships confirm the influence of service quality on customer satisfaction of the Islamic bank in Tripoli, Libya.